2021
DOI: 10.21203/rs.3.rs-433071/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Knowledge, Perception and Attitude in Relation to Climate Change: A Cross-sectional Survey

Abstract: A cross-sectional online survey was conducted using multiple online channels, where hundreds of responses were recorded from seven different countries, in order to provide a better understanding of the global public opinion about the awareness, perception and attitude about climate change. The results reflected that majority of people believe in the actual happening of Climate Change both by natural as well as anthropogenic causes. While most respondents believed in the anthropogenic causes of climate change, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…Nonetheless, evidence has been mixed regarding whether trait optimism or closely related constructs, such as hope and future subjective wellbeing, are reliably associated with greater PEB (Ojala, 2012(Ojala, , 2015Kaida, 2016a,b, 2017). Similar mixed findings have been reported for the relations among support for geoengineering technologies, optimism, and engagement in conservation behavior (Murtagh et al, 2015;Rehman et al, 2021). Most of the research on the associations between subjective wellbeing, optimism-pessimism, and PEB has been crosssectional, precluding an examination of "true" causal mechanisms.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Nonetheless, evidence has been mixed regarding whether trait optimism or closely related constructs, such as hope and future subjective wellbeing, are reliably associated with greater PEB (Ojala, 2012(Ojala, , 2015Kaida, 2016a,b, 2017). Similar mixed findings have been reported for the relations among support for geoengineering technologies, optimism, and engagement in conservation behavior (Murtagh et al, 2015;Rehman et al, 2021). Most of the research on the associations between subjective wellbeing, optimism-pessimism, and PEB has been crosssectional, precluding an examination of "true" causal mechanisms.…”
Section: Discussionsupporting
confidence: 60%
“…Some have posited a reliance on science and technology to solve environmental ills is problematic and may breed complacency and inaction regarding conservation behavior (Dunlap et al, 2000;Murtagh et al, 2015;Mittiga, 2019). Nonetheless, support for geoengineering technologies to abate climate change has been linked with expressing concern for the environment (Landry et al, 2018), and people seem to express optimism toward to efficacy of geoengineering interventions to mitigate environmental dilemmas (Rehman et al, 2021). We found that optimistic environmental messaging promoted support for geoengineering via heightened state optimism (Hypothesis 2).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation